Educational trajectories of immigrant-origin youths in Finland: a mixed methods analysis. Issue 7 (17th November 2018) - Holmberg, Liila; Kalalahti, Mira; Varjo, Janne; Kivirauma, Joel; Mäkelä, Marja-Liisa; Saarinen, Minna; Zacheus, Tuomas; Jahnukainen, Markku
ABSTRACT: This article examines the educational trajectories envisioned by immigrant-origin youths. The mixed-methods research draws upon quantitative (N = 445) and interview data (n = 112). Whereas most prior research focuses on educational achievement or educational attainment of immigrant-origin youth, this article focuses on their outlooks concerning education and occupation. We determined the educational and career aspirations and expectations immigrant-origin youths have and in the ways their aspirations differ from those of Finnish-origin youths. We also seek to discover how this possible aspiration paradox is reflected in the trajectories envisioned by immigrant-origin youths. We confirm earlier findings showing that immigrant-origin youths have both a strong belief in education and the will to achieve success in tertiary-level education. We also argue for diversity of vocationally oriented youth: whereas Finnish-origin youths often share determinate vocational outlooks, immigrant-origin youths are more likely to aim for tertiary education via vocational education.